Prospects for supporting regional integration effectively : an independent analysis of the European Union's approach to the 11th European Development Fund regional programming - Herrero, Alisa (CEDPM MaastrichtNL, 2016)
Aims to understand the key drivers behind the EU's approach to and support for regional cooperation as devised for the 11th EDF; to provide a critical insight into the main innovations and the prospects for delivering better results in regional integration; to shed light on the EU-ACP partnership throughout the process, with a particular focus on how aid and development effectiveness principles were translated into practice; to explore how EU interinstiutional relations played out in the 11th EDF regional programming process; and to reflect on what the findings mean for the EU, at a time when it is defining a global strategy for its common foreign and security policy (CFSP) and the European Consensus on Development.